Type, source, adequacy and outcome of consultations requested from the department of general surgery: a retrospective cohort study - Leblebici, Metin; Alimoğlu, Orhan (The European Research Journal, 2021)
Objectives: To evaluate consultations requested from the department of general surgery in terms of type, source and adequacy and outcome regarding general surgery practice. Methods: A total of 4706 consultations requested from the department of general surgery during the 2019 calendar year were included in this retrospective study. Data on patient demographics, type of consultation (urgent, routine), the requesting clinic, time of request, response time to consultation request (min), diagnosis and management of consulted patients by general surgery clinic and survivorship status were recorded. Results: Consultations were urgent (69.0%) and made outside office hours (66.0%) in most of cases and more commonly requested by the emergency department (67.5%). The surgical pathology was confirmed only in 1338 (28.4%) consultations, while more commonly for urgent vs. routine requests (37.4 vs. 8.5%, p = 0.001), for consultations requested by emergency department (ranged 30.9 to 40.0%) vs. other clinics (ranged 0.0% to 19.1%, p = 0.001) and for diseases of colon-rectum-anus (100.0%, p = 0.001) than other disorders. The likelihood of urgent consultations (72.0% vs. 37.3%, p = 0.001) and post-consultation inpatient management (90.5% vs. 24.7%, p = 0.001) and were more likely among survivors vs. non-survivors. Conclusions: In conclusion, our findings revealed that most of the consultations were urgent, outside the office hours and outpatient consultations requested by the emergency department, while surgical pathology was confirmed only in one third of consultations. Our findings indicate improved consultation practice particularly for routine requests by non-emergency clinics to prevent the incompatible or unnecessary consultation requests and related healthcare resource utilization.